2017
DOI: 10.1158/1078-0432.ccr-16-2022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Acquired Drug Resistance to the HDAC6 Selective Inhibitor Ricolinostat Reveals Rational Drug-Drug Combination with Ibrutinib

Abstract: Purpose Pan-class I/II histone deacetylase (HDAC) inhibitors are effective treatments for select lymphomas. Isoform-selective HDAC inhibitors are emerging as potentially more targeted agents. ACY-1215 (ricolinostat) is a first in class selective HDAC6 inhibitor. To better understand the discrete function of HDAC6 and its role in lymphoma, we developed a lymphoma cell line resistant to ACY-1215. Experimental Design The diffuse large B-cell lymphoma cell line OCI-Ly10 was exposed to increasing concentrations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The development of a multi-target drug may overcome these side effects. HDAC inhibitors have been verified for cancer cell growth inhibition, cell apoptosis inducement, cell invasion, and metastasis suppression ( Amengual et al, 2015 , 2016 ). Currently, four HDAC inhibitors are approved by the FDA for T-cell lymphoma and multiple myeloma ( Kawaguchi et al, 2003 ; Aldana-Masangkay and Sakamoto, 2011 ; Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of a multi-target drug may overcome these side effects. HDAC inhibitors have been verified for cancer cell growth inhibition, cell apoptosis inducement, cell invasion, and metastasis suppression ( Amengual et al, 2015 , 2016 ). Currently, four HDAC inhibitors are approved by the FDA for T-cell lymphoma and multiple myeloma ( Kawaguchi et al, 2003 ; Aldana-Masangkay and Sakamoto, 2011 ; Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a preclinical study identified the synergistic interaction of ricolinostat and ibrutinib the first-in-class BTK (Bruton's tyrosin kinase) inhibitor in a large panel of lymphoma cell lines and in a xenograft model of lymphoma. This combination led to a marked tumor growth delay and prolonged overall survival (Amengual et al, 2017).…”
Section: Selective Hdacis In Combination With Tyrosine Kinase Pathwaymentioning
confidence: 99%
“…Ricolinostat is the first oral selective HDAC6 inhibitor with reduced class I HDAC activity to be studied clinically, and it might partner well with other compounds to enhance their efficacies in treating diverse cancers. Although the results from experimental or preclinical studies have shown that combinations of ricolinostat with lenalidomide, ibrutinib, carfilzomib or bortezomib can exert synergistic effects in multiple myeloma, DLBCL, and mantle cell lymphoma , the combination of ricolinostat with a MET inhibitor (METi) has not been investigated in DLBCL.…”
Section: Introductionmentioning
confidence: 99%